Acute purulent otitis media: features of development of complications in the form of neuritis of the facial nerve - Z. N. Lovpache; S. M. Chudopal; E. S. Ulimbasheva; T. M. Aliev (Лечащий Врач, 2025)
Background. Neuritis of the facial nerve is a rare complication of acute purulent otitis media, which, in addition to the symptoms of otitis media, is accompanied by dysfunction of facial muscles, facial asymmetry, ophthalmological disorders, etc. Opinions regarding the pathophysiologic mechanisms of the complication include anatomic variations of the facial nerve, retrograde infection, exposure of the nerve to bacterial and viral toxins, and impaired blood supply to the nerve due to thrombosis or compression of the vessels feeding it. The complication reduces the quality of life by 2-3 months, can have long-term consequences and requires timely diagnosis and treatment in conditions of consolidation of specialists of various profiles. The course and outcomes of the disease depend on the aggressiveness of the infectious agent, timely diagnosis, adequate antibacterial and other therapy, and the state of the patient's immune system.Objective. Generalization and systematization of current data on pathogenesis, clinical manifestations, diagnostic methods and treatment of facial nerve neuritis of otogenic origin; presentation of a clinical case of facial nerve lesion in an adult patient with acute purulent otitis media.Results. A comprehensive analysis of the existing theories of the pathophysiology of facial neuritis of otogenic origin; the main conservative and surgical approaches to the treatment of the disease; and the role of non-drug therapy is described. The article also presents a clinical case of facial nerve damage in an adult patient with acute purulent otitis media.Conclusion. Despite the rarity of the described complication, timely diagnosis and adequate treatment are required to achieve a favorable outcome and prevent chronic neurological consequences. Efforts to improve the quality of treatment of the underlying disease, the development of strategies for interaction between various specialists, combined with strict adherence to the treatment regimen by patients with otitis media can lead to success in the fight against facial nerve neuritis of otogenic genesis.